(untitled) (Journal of Dhaka Medical College, 2018)
Background: Iron deficiency anaemia is a common problem in antenatal patient especially in primigravida in developing world. The study was conducted to evaluate the efficacy of intravenous iron sucrose in antenatal primigravida anaemic cases. Aims and Objectives: The study was conducted to evaluate the response of intravenous iron therapy in anaemic antenatal primigravida patients. The rise of hemoglobin level was predicted after therapy. Materials and Methods: A prospective cross-sectional study was done in the antenatal clinic of Popular Medical College Hospital from January 2016 to December 2016. Primigravida women of e” 18 years with iron deficiency anaemia were included in this study. Pretreatment hemoglobin level was measured. After total dose of calculated iron, intravenous iron sucrose was infused to achieve the target hemoglobin. After completion of therapy hemoglobin was measured 2 weeks and 4 weeks after last dose of iron treatment. Mean, percentage, Chi-square test was done and P value <0.05 was considered significant. Results: Among the 63 primigravida anaemic patients mean age of the study subjects were 23.98 years with mean gestational age were 23.54 weeks. Their pretreatment hemoglobin level was 5.42 gm/dl. After total dose infusion of iron sucrose, the mean rise of hemoglobin after 2 weeks was 8.87 gm/dl and after 4 weeks was 10.87 gm/dl respectively. This findings were statistically significant (P<0.001). Attainment of target hemoglobin at the range of 9.1-11.0 gm/ dl was 50.79% and 65.08% after 2 weeks and 4 weeks respectively. Conclusion: Parenteral iron therapy in the form of iron sucrose proved to be better choice to correct iron deficiency anaemia in primigravida anaemic patients J Dhaka Medical College, Vol. 27, No.1, April, 2018, Page 79-82